Statistics Enthusiast Movement: Enhancement of Posyandu and PKK Cadre Competencies in Desa Simpang Tiga for Monitoring Maternal and Child Health : Gerakan Cinta Statistik: Peningkatan Kompetensi Kader Posyandu dan PKK Desa Simpang Tiga dalam Pemantauan Kesehatan Ibu dan Anak - Anggraini, Dewi; Rahkmawati , Yeni; Zulliati, Zulliati; Maulida, Maisya; Cahyadi, Rizqa Nabiilah; Nazili, Muhammad Haqin; Al Atqiaa , Muhammad Azkaa; Siahaan, Priscilla Aquirera Iory; Viranty, Miftah Rizky (Universitas Lancang Kuning, 2025)
Local area monitoring of maternal and child health is crucial for assessing health service quality. In Desa Simpang Tiga, challenges include a manual and unintegrated maternal and child health documentation system and limited cadre competencies in anthropometric measurements, antenatal care data management, and analysis. This community-based empowerment program aimed to address these issues through community partnership empowerment. The program involved focus group discussions and scientific and technical training for Posyandu and PKK cadres. A Wilcoxon Test evaluated the program's effectiveness by comparing pre- and post-training cadre competencies. Results showed significant improvements: cadre competency in anthropometric measurements increased by 20.8% (from 53% to 73.8%) (p < 0.05). Competency in maternal and child health data management and analysis increased by 43.8% (from 33.5% to 77.3%) (p < 0.05). These findings demonstrate the program's success in enhancing cadre competencies in basic maternal and child health measurements and data management in Desa Simpang Tiga.